Soft-balancing: SADC Former Liberation Movements’ Responses to the Imposition of Sanctions on Zimbabwe 2002 -2015 - Panganayi, More; Marovah, Tendayi (Quest Journal of Management and Social Sciences, 2020)
Background: This paper addresses a popular dichotomous African nationalist and independentist approaches to foreign policy mainly characterised by soft balancing and quiet diplomacy. This dichotomous approach has been dominated by the need to maintain independence from resurgent neo-colonial claws by promoting African agenda. The African nationalist and independentist prism are used to interrogate the misconceptions created by the resurgence of meetings of former liberation movements in Southern Africa. Objective: This paper aims to proffer alternative political survival tools that can be adopted by the weak global south states against resurgent neo-colonialism. Methods: Using the work of Machiavelli on international anarchy complemented by the soft balancing as a real-power politics theory, the paper offers alternative lenses to interpretation of impact of sanctions and subsequent strategic alliances formed after 2002 in Southern Africa. Findings: Depending on the dominant realist paradigm to analyse sanctions imposed on Zimbabwe, the paper confirms the anarchic nature of international society and that the formation of alliances was not an ad hoc reaction. Conclusions: Arguing that the world is anarchic and there is no international arbiter, the paper recommends soft balancing as a political survival strategy. Implications: This paper can be useful to concerned authorities of Zimbabwe in planning appropriate policies post sanction. For that purpose this study can serve as reference.